2021
DOI: 10.3847/1538-4357/abcb8e
|View full text |Cite
|
Sign up to set email alerts
|

On the Collisional Disalignment of Dust Grains in Illuminated and Shaded Regions of IC 63

Abstract: Interstellar dust grain alignment causes polarization from UV to mm wavelengths, allowing the study of the geometry and strength of the magnetic field. Over last couple of decades observations and theory have led to the establishment of the Radiative Alignment Torque (RAT) mechanism as leading candidate to explain the effect. With a quantitatively well constrained theory, polarization can be used not only to study the interstellar magnetic field, but also the dust and other environmental parameters. Photo-diss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Results obtained from modeling and observations of dust polarization of the diffuse ISM and dense cores tend to favor the scenario where the efficiency of RATs can only be reproduced if grains' magnetic relaxation is sufficiently fast, i.e., for superparamagnetic grains (Hoang & Lazarian 2016;Le Gouellec et al 2020;Reissl et al 2020). We also note that H 2 formation occurring at the grains' surfaces provides additional torque that also increase the grain rotational velocity, eventually bringing the grain to suprathermal rotation (Purcell 1979;Hoang et al 2015), especially toward PDRs (Le Bourlot et al 2012;Andersson et al 2013;Soam et al 2021). These both effects of grains' super-paramagneticity and H 2 formation supplemental torque increase the fraction of grains with high angular momentum, i.e., the fraction of grains at the the so-called high-J attractor point (Lazarian & Hoang 2007;Hoang & Lazarian 2009b.…”
Section: Grain Size Parameter Space For K-ratmentioning
confidence: 65%
“…Results obtained from modeling and observations of dust polarization of the diffuse ISM and dense cores tend to favor the scenario where the efficiency of RATs can only be reproduced if grains' magnetic relaxation is sufficiently fast, i.e., for superparamagnetic grains (Hoang & Lazarian 2016;Le Gouellec et al 2020;Reissl et al 2020). We also note that H 2 formation occurring at the grains' surfaces provides additional torque that also increase the grain rotational velocity, eventually bringing the grain to suprathermal rotation (Purcell 1979;Hoang et al 2015), especially toward PDRs (Le Bourlot et al 2012;Andersson et al 2013;Soam et al 2021). These both effects of grains' super-paramagneticity and H 2 formation supplemental torque increase the fraction of grains with high angular momentum, i.e., the fraction of grains at the the so-called high-J attractor point (Lazarian & Hoang 2007;Hoang & Lazarian 2009b.…”
Section: Grain Size Parameter Space For K-ratmentioning
confidence: 65%
“…Whereas EXES observations are further capable of resolving temperature of PDRs. Soam et al (2021) showed that the collisional disalignment rate of the dust grains causing the observed polarization follow a bifurcated relation with respect to the gas density. The two observed sequences in derived disalignment rate correspond to lines of sight in front and behind gas clumps, as seen in the HCO + (J=1-0) map of the cloud.…”
Section: Discussionmentioning
confidence: 97%
“…We also used HCO + (J = 1-0) position-position-velocity maps observed with CARMA 9 (Soam et al 2021b) , and molecular hydrogen H 2 (1-0)S(1) mapping from CFHT 10 (Andersson et al 2013) in conjunction with low-resolution 12 CO (1-0) data from TRAO 11 as part of a molecular line survey of 16 BRCs by A. Soam et al (2023, in preparation) to help in studying the gas locations at different opacities.…”
Section: Data Acquisition and Reductionmentioning
confidence: 99%
“…These investigations were done to understand the magnetized evolution of these nebulae. Polarization efficiency and collisional disalignment of dust grains in IC 63 are studied by Soam et al (2021d) and Soam et al (2021a), respectively. The gradients in temperature and densities in the PDR region of IC 63 are also studied by Soam et al (2021c) using pure rotational molecular hydrogen observations.…”
Section: Introductionmentioning
confidence: 99%